A critical role for HNF4α in polymicrobial sepsis-associated metabolic reprogramming and death - Céline Van Dender; Steven Timmermans; Ville Paakinaho; Tineke Vanderhaeghen; Jolien Vandewalle; Maarten Claes; Bruno Garcia; Bart Roman; Jan De Waele; Siska Croubels; Karolien De Bosscher; Philip Meuleman; et al. (EMBO Molecular Medicine)
Abstract In sepsis, limited food intake and increased energy expenditure induce a starvation response, which is compromised by a quick decline in the expression of hepatic PPARα, a transcription factor essential in intracellular catabolism of free fatty acids. The mechanism upstream of this PPARα downregulation is unknown. We found that sepsis causes a progressive hepatic loss-of-function of HNF4α, which has a strong impact on the expression of several important nuclear receptors, including PPARα. HNF4α depletion in hepatocytes dramatically increases sepsis lethality, steatosis, and organ damage and prevents an adequate response to IL6, which is critical for liver regeneration and survival. An HNF4α agonist protects against sepsis at all levels, irrespectively of bacterial loads, suggesting HNF4α is crucial in tolerance to sepsis. In conclusion, hepatic HNF4α activity is decreased during sepsis, causing PPARα downregulation, metabolic problems, and a disturbed IL6-mediated acute phase response. The findings provide new insights and therapeutic options in sepsis.